The baby-sitters club. 12, Jessi's secret language - Chau, Chan; Martin, Ann M., 1955- (New York, NY : Graphix, 2022)
Jessi recently moved to Stoneybrook and is one of the newest members of The Baby-sitters Club. She's getting ready to start regularly sitting for the BSC's newest charge, Matt Braddock. Matt has been deaf since birth and uses sign language to communicate, so Jessi has to use it, too. It's a secret language! Soon all the neighborhood kids want to learn how to sign, which keeps the BSC busy. Jessi's the busiest of all--she's preparing for her dance school's big show, plus working on another secret, just for Matt. Will Jessi be able to keep the secret and pull off her special event?"--Provided by publisher.
Based on: Jessi's secret language / Ann M. Martin.
3.6
3-6
GN450L
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc -- Juvenile fiction; Babysitters -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Clubs -- Comic books, strips, etc -- Juvenile fiction; Babysitters Club (Imaginary organization) -- Fiction; Babysitters and babysitting -- Fiction; Friendship -- Fiction; Clubs -- Fiction; Cartoons and comics; Graphic novel adaptations; Graphic novels; Comics (Graphic works)